(untitled) (Conference on English Language Teaching, 2023)
MBKM is new curriculum initiated by Indonesia Minister Mr Nadiem Makarim. Certainly MBKM has various program, namely Kampus Mengajar, Kewirusahaan Merdeka, Praktisi Mengajar, untill Program Pertukaran Mahasiswa Merdeka (PMM). Inconnections with several programs that contained in MBKM learning. In this research discusses about the perspective of students in student’s exchange program (PMM). The reseacher is reseach the perpsective of inbound from various collage. Totally 30 students are used as sampling of this research. The technique that used in collecting sampling is a simple random sampling. The method that used in the research is descriptif quantitatif method, the object of research is given a questionnaire which contains questions that related to research subject. The result of the research is 83% students get the effectivness in teaching leraning target’s of univerity, 77% PMM students think that there is a compability of lesson and teaching material with their base university. While 94% of PMM students think that there is a culture shocks in the teaching learning activities of university’s destination.